Differences between recent and historical records of upper species limits in the northern European Alps - Schmidtlein, Sebastian; Faude, Ulrike; Rößler, Ole; Feilhauer, Hannes; Ewald, Jörg; Meyn, Andrea; Schmidt, Johannes (ERDKUNDE, 2013)
Are there differences in historical and recent upper range limits of vascular plants and are such differences more pronounced in individual species groups? The limits of 1103 plants of the Northern Alps are compared to range limits in the mid-19th century. The comparison is based on two surveys. The first survey was conducted by Otto Sendtner in 1848–1853, the second in 1991–2008 during a habitat inventory. To our knowledge this is the first comparative studies reaching back to the end of the “Little Ice Age” and comprising an almost entire regional flora covering the complete range of habitats. During the recent survey, most species were found at higher elevations. Even though the differences fit well with the expected shifts due to climate warming we cannot exclude effects of sampling bias. However, we assume that the relative differences between species groups can be safely interpreted. The differences in upper limits between both surveys were significantly larger among forest species. The most important reason is probably discontinued pasture and mowing, which may have amplified possible warming effects. Nitrogen deposits may have contributed to this effect by placing competitive species in a more advantageous position.